PENGARUH KERJA SAMA TIM TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KOTA BIMA - Zulkiflin; muhammad yusuf; feni aryani (Publika Citra Media, 2026)
This study aims to determine the Effect of Teamwork on the Work Performance of Employees of the Bima City Environmental Service. The approach used in the study is an associative approach. The population in the study amounted to 70 people with a sample of 40 people. Data collection techniques used were observation, questionnaires, and literature studies. Data analysis techniques used were validity and reliability tests, simple linear regression analysis, correlation coefficients, determination coefficients, T tests processed using the Statistical Product and Service Solution (SPSS) version 20 program. The results of the study showed that Teamwork (X1) had a significant effect on the Work Performance of Employees of the Bima City Environmental Service.